Multiobjective optimal FLC driven hybrid mass damper system for torsionally coupled, seismically excited structures. - Ahlawat, A.S (Earthquake engineering & structural dynamics.)
In most of the research work on structural vibration control only two dimensional plane structural modelling has been considered, although only a few practical building structures can be modelled as planar structures. Therefore, these methods are not directly applicable to the majority of the practical building structures. This paper discusses the design of multiobjective optimal fuzzy logic controller (FLC) driven hybrid mass damper (HMD) system for seismically excited torsionally coupled building structures. Floor acceleration and velocity information have been used as feedback to the fuzzy logic controller. A three branch tournament Genetic Algorithm has been used for the multiobjective optimal design of the FLC driven HMD system, where the minimization of the non dimensionalized peak displacement, acceleration and rotation of the structure about its vertical axis, have been as the three objective functions. The proposed multiobjective optimal fuzzy logic controller has been verified for an example problem reported in the literature. This HMD system consists of four HMDs arranged in such a way that the system can control the torsional mode of vibration effectively in addition to the flexure modes of vibration.